Assessing the efficacy of anticoagulation therapy in the management of atrial fibrillation: An observational study - Swathi G,; Yerakala Ramesh,; Pragna S, (Asian Journal of Medical Sciences, 2024)
Background: Atrial fibrillation (AF) substantially elevates stroke risk. Managing AF with anticoagulation therapy is crucial to reduce this risk, yet assessing the balance between its efficacy in preventing strokes and the potential for bleeding complications is essential. Aims and Objectives: The aim of this study is to evaluate the efficacy and safety of anticoagulation therapy in the management of AF. Materials and Methods: This observational study followed 100 AF patients at a government general hospital over 8 months to evaluate the efficacy and safety of anticoagulation therapy. We analyzed stroke occurrence, bleeding complications, treatment adherence, patient satisfaction, and improvements in quality of life (QoL). In addition, we recorded patient demographics and baseline characteristics, such as body mass index, smoking status, and CHA2DS2-VASc scores. Results: The study population was at a moderate-to-high risk of stroke, with an average CHA2DS2-VASc score of 2.9. The efficacy of stroke prevention was confirmed, with a 2% incidence of stroke events. Bleeding complications included major bleeding in 4% of the patients, with minor bleeding predominantly occurring in the first 3 months of therapy. Treatment adherence was noteworthy, with 75% of patients not missing any doses. High levels of patient satisfaction were observed, with 90% of participants reporting being satisfied or very satisfied with their treatment. QoL, measured through the AF-QoL questionnaire, showed significant improvement from a baseline score of 58–76. Conclusion: Anticoagulation therapy in AF patients was effective in stroke prevention with a manageable risk of bleeding. High treatment adherence and patient satisfaction further support the therapeutic value of anticoagulation in AF management.